Strategies of containment a critical appraisal of American national security policy during the Cold War - Gaddis, John Lewis (Oxford University Press, 2005)
A classic synthesis of US security policy, now updated to include analysis of how Reagan, Bush Snr., Clinton, & Bush Jnr. have defended the nation.